Hypoglycemic activity of aqueous leaf extract of Limonia elephantum in alloxan-induced diabetic rats (Bangladesh Journal of Pharmacology, 2014)
The hypoglycemic activity of the aqueous leaf extract of Limonia elephantum was evaluated. The extract was administered orally 1,000 mg/kg to normal and alloxan-induced (55 mg/kg body weight, i.v) diabetic rats. The hypoglycemic effect of the extract was statistically significant with an oral dose of 1,000 mg/kg and was comparable to that of the effect produced by standard antidiabetic agent, metformin 1.5 mg/kg. The extract increased the glucose tolerance using oral glucose tolerance test.